Emlyn's moon [compact disc, unabridged] - Nimmo, Jenny (Nimmo, Jenny. Magician trilogy, 2006)
Young magician Gwyn and his friend Nia have been warned to stay away from Emlyn Llewelyn, the strange boy who claims his mother lives in the moon. And yet, a mysterious magic continues to draw them to him. But why?